Emerging Role of Cancer-Associated Fibroblasts-Derived Exosomes in Tumorigenesis - Peng, Lushan; Wang, Dan; Han, Yingying; Huang, Tao; He, Xiaoyun; Wang, Junpu; Ou, Chunlin (Frontiers in Immunology, 2022)
Cancer-associated fibroblasts (CAFs) are the most important component of the stromal cell population in the tumor microenvironment which plays an irreplaceable role in oncogenesis and progression. Exosomes, a class of small extracellular vesicles (EVs), can transfer biological information (e.g., proteins, nucleic acids, and metabolites) from secreted cells to target recipient cells, thereby affecting the progression of human diseases, including cancers. Recent studies have demonstrated that CAF-derived exosomes play a crucial role in tumorigenesis, including tumor malignant proliferation, metastasis, drug resistance, and immune response. Moreover, the aberrant expression of CAF-derived exosomal noncoding RNA, and proteins is closely related to the clinical pathological characterizations of patients with tumor. Gaining deeper insight into the role of CAF-derived exosomes in tumorigenesis may provide novel diagnostic biomarkers and therapeutic targets for human cancers.